Pengaruh Profitabilitas, Likuiditas, Leverage, Ukuran Perusahaan Dan Nilai Pasar Terhadap Return Saham Perusahaan Sektor Industri Barang Konsumsi Di BEI - Avivah Inaroh Nahdhiyah; Siti Alliyah (Accounting Global Journal, 2023)
The purpose of this studied was to determine the impact of profitability, liquidiy, leverage, firm size and market value on stock returns. This studied use purposive sampling in order to obtain a sample of 18 the consumer goods industry sector entities registered with IDX in 2017-2021. Methods of data collection using documentation. The data analysis technique uses multiple linier regression analysis using the SPSS 26 application. The result of this study indicate that profitability has a positive significant effect on stock returns. liquidity has negative effect and hasn’t significant effect on stock returns. Company size has negative significant effect on stock returns, on the other hand, leverage and market value have a positive hasn’t significant effect on stock returns.Keyword : Profitability, Liquidity, Leverage, Size, Market Value.